Accuracy of 3D-planned patient specific instrumentation in high tibial open wedge valgisation osteotomy - Fucentese, Sandro F. (J Exp Orthop, 2020)
PURPOSE: High tibial osteotomy (HTO) is an effective treatment option in early osteoarthritis. However, preoperative planning and surgical execution can be challenging. Computer assisted three-dimensional (3D) planning and patient-specific instruments (PSI) might be helpful tools in achieving successful outcomes. Goal of this study was to assess the accuracy of HTO using PSI. METHODS: All medial open wedge PSI-HTO between 2014 and 2016 were reviewed. Using pre- and postoperative radiographs, hip-knee-ankle angle (HKA) and posterior tibial slope (PTS) were determined two-dimensionally (2D) to calculate 2D accuracy. Using postoperative CT-data, 3D surface models of the tibias were reconstructed and superimposed with the planning to calculate 3D accuracy. RESULTS: Twenty-three patients could be included. A mean correction of HKA of 9.7° ± 2.6° was planned. Postoperative assessment of HKA correction showed a mean correction of 8.9° ± 3.2°, resulting in a 2D accuracy for HKA correction of 0.8° ± 1.5°. The postoperative PTS changed by 1.7° ± 2.2°. 3D accuracy showed average 3D rotational differences of − 0.1° ± 2.3° in coronal plane, − 0.2° ± 2.3° in transversal plane, and 1.3° ± 2.1° in sagittal plane, whereby 3D translational differences were calculated as 0.1 mm ± 1.3 mm in coronal plane, − 0.1 ± 0.6 mm in transversal plane, and − 0.1 ± 0.6 mm in sagittal plane. CONCLUSION: The use of PSI in HTO results in accurate correction of mechanical leg axis. In contrast to the known problem of unintended PTS changes in conventional HTO, just slight changes of PTS could be observed using PSI. The use of PSI in HTO might be preferable to obtain desired correction of HKA and to maintain PTS.